Safety and efficacy of sofosbuvir based regimen in the treatment of hepatitis C virus infection among hemodialysis patients in Morocco - Tamzaourte, Mouna; Zajjari, Yassir; Berrag, Sanae; Adioui, Tarik; Aourarh, Aziz; Kabbaj, Driss El (Journal of Clinical Nephrology, 2021)
The introduction of a new class of drugs known as direct acting antiviral (DAA) agents represents a revolution in the treatment of hepatitis C virus (HCV) in the general population, as these regimens are associated with higher sustained virological response (SVR) rates and fewer side effects. However, for patients with advanced chronic kidney disease suffering from HVC infection, treatment options including DAA remain limited. The aim of this study is to report our experience on Sofosbuvir (SOF) based regimen in the treatment of HCV in hemodialysis patients. In this observational study, we included all patients with chronic HCV infection on hemodialysis who were treated with SOF in our Hospital between April 2016 and March 2018. All patients were treated with a combination of 400 mg of SOF three times a week after hemodialysis and of 60 mg of Daclatasvir daily for a total of 12 to 24 weeks. A total of 20 hemodialysis patients were included in this study. 12 were females and the mean age was 52.1 ± 15.5 years. 11 patients were infected with HCV genotypes 1b. All patients achieved SVR. Clinical and biological tolerance was very good for all patients and none of them had to discontinue treatment because of side effects or developed hepatobiliary and cardiac toxicity. Two patients reported fatigue and another patient reported headaches. However, these symptoms were spontaneously resolved after the end of the treatment. In Morocco, despite the absence of new DAA combination treatment regimens which are not renally eliminated, our study concludes that SOF based treatment without Ribavirin or Peginterferon was effective and safe with minimal side effects. However, larger studies are still needed in order to validate these results.